Collaborative Governance in Kelompok Wanita Tani (KWT) Women's Empowerment Programs to Realize Food Security in Cilegon City - Farah Fatika Sari (International Journal of Social Sciences Review, 2022)
This study describe the process and implementation of the Collaborative governance program in the Kelompok Wanita Tani program is one of the main breakthroughs in providing family food security through yardland in Cilegon City. This is because the increase in food prices has experienced a spike. After all, the world's food reserves are experiencing a crisis, especially during the pandemic. This research aims to analyze the concept of Collaborative governance in the KWT program, understand the pattern of collaboration actors in the KWT program's implementation, and know the inhibiting and driving factors in the Collaborative governance process. By using the theory of Collaborative governance, Ansell and Gash, with the Collaborative governance Model, which includes: face-to-face dialogue, building trust, shared commitment, shared understanding, achievement of results, obtained the theoretical analysis which shows that the Collaborative governance process has not been distributed equally on KWT program in Cilegon City. It can be proved by the fact that there is no monitoring and evaluation schedule for KWT capital assistance that is given to all KWT in Cilegon City to execute the programs to actualize family food security, the lack of maintenance carried out by the government in increasing the participation of each member of the Kelompok Wanita Tani, there is still a lack of support from the sub-district government due to lack of understanding of the role in the KWT program, there are still KWT programs that did not make in a long-term collaboration between collaborating actors which caused the program only runs at the beginning of the program. Also, there is no harvest innovation product from all KWT in Cilegon City. This research hopes that it can be used as an evaluation material and tighten monitoring of the KWT program to actualize food security.